Attack Intensity Variety of Coffea arabica and Coffea canephora Hypothenemus hampei Ferrari, 1867 (Coleoptera: Curculionidae: Scolytinae) in North Sumatra - Elida Hafni Siregar; Aida Fitriani Sitompul; Syarifuddin; Yusron Efendi (Future Science, 2023)
Coffee is one of the export commodities of the State of Indonesia, a foreign exchange earner besides oil and gas so that it has an important role in economic activities in Indonesia. The main problem with smallholder coffee plantations is the low productivity and quality to meet export standards. One of the causes is pest attack which also causes economic loss. The coffee berry borer (Hypothenemus hampei Ferrari) is one of the main causes of the decline in coffee production in Indonesia, even in all coffee-producing countries in the world. The purpose of this study was to analyze the attack intensity of the coffee berry borer (H. hampei) on Coffea arabica and Coffea canephora plants in North Sumatra. The research was conducted in Karo, Dairi, Samosir, Humbahas, Taput, Tapsel, Toba, and Simalungun districts spread over fifteen locations. Sampling in this study was carried out exploratively with the Random Sampling method. The results showed that the highest attack intensity of H. hampei on C. arabica was at Paranjulu (56 %) with an altitude of 949 mdpl; and on C. canephora was at Marihat Huta (62 %) with an altitude of 898 mdpl. Huta Galung in Samosir district with an altitude of 1759 mdpl did not find attack intensity H. hampei. The conclusion showed that altitude affected the attack intensity of H. hampei